Fire safety in military vehicles – Evaluation of ISO 3795 - Svebrant,Johan (LUTVDG/TVBB-5370-SE, 2011)
This work has evaluated ISO 3795. It was found that ISO 3795 isn’t a suitable method to test interior materials and its use has led to a low level of fire safety in military vehicles. A different test method to be used for fire testing interior materials in military vehicles was suggested; ISO 5660 cone calorimeter. Eleven different interior materials from two military vehicles were tested in the cone calorimeter at 25 and 50 kW/m2. Time to ignition was found to be short and the heat release rate to be high. The materials were evaluated according to criteria used for trains, high speed crafts and submarines. Only one material passed, but only for use on trains and only according to the criterion for 25 kW/m2, and not the criterion for 50 kW/m2. All other materials failed. A comparison was made with materials from cars and buses which have been tested earlier in other studies. It was found that materials from military vehicles ignite just as fast, or faster, but have a lower heat release rate.
Keywords: ISO 3795; ISO 5660; cone calorimeter; FMVSS 302; test method; heat release rate; HRR; time to ignition; interior materials; military vehicles; fire safety; fire tests